2020
DOI: 10.3390/molecules25153429
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive and Cytotoxic Activity of Opioid Peptides with Hydrazone and Hydrazide Moieties at the C-Terminus

Abstract: In the present contribution, we analyze the influence that C-terminal extension of short opioid peptide sequences by organic fragments has on receptor affinity, in vivo analgesic activity, and antimelanoma properties. The considered fragments were based on either N-acylhydrazone (NAH) or N′-acylhydrazide motifs combined with the 3,5-bis(trifluoromethyl)phenyl moiety. Eleven novel compounds were synthesized and subject to biological evaluation. The analyzed compounds exhibit a diversified range of affinities fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…At MOR, the most populated cluster (with respect to the positioning of the opioid part) closely resembles the experimental positioning of DAMGO in this receptor. Similar binding poses were also proposed based on molecular modelling results for the opioid fragment of other opioid/antitachykinin hybrids [17] or some Tyr-d-Ala-Phe-Phe (TAPP) derivatives [66]. Aromatic rings of BU72 (experiment [67]), fentanyl (modelling [68]) cyclic opioid derivatives (modelling [69]), or linear peptide opioids (modelling [70]) were found to be located similarly as the Phe 4 ring in MOR-1 pose.…”
Section: Discussion Of the In Silico Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…At MOR, the most populated cluster (with respect to the positioning of the opioid part) closely resembles the experimental positioning of DAMGO in this receptor. Similar binding poses were also proposed based on molecular modelling results for the opioid fragment of other opioid/antitachykinin hybrids [17] or some Tyr-d-Ala-Phe-Phe (TAPP) derivatives [66]. Aromatic rings of BU72 (experiment [67]), fentanyl (modelling [68]) cyclic opioid derivatives (modelling [69]), or linear peptide opioids (modelling [70]) were found to be located similarly as the Phe 4 ring in MOR-1 pose.…”
Section: Discussion Of the In Silico Resultsmentioning
confidence: 54%
“…These include our previous contribution on AA3266 [29] and the above mentioned AWL3020 [44]. Recently Dyniewicz et al reported a series of hybrid compounds in which various opioid sequences were appended (at the C-terminus) with the 3,5-bis(trifluoromethyl)phenyl moiety characteristic for neurokinin-1 antagonists [17]. The compounds turned out to have very low or negligible rat NK1R affinity.…”
Section: Discussion Of the In Vitro Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Further studies have shown that only one tetrapeptide with a hydrazide bridge and phenylalanine residue from the other tetrapeptide is responsible for the biological properties of biphalin [ 19 ]. The results were used to design and then synthesize a series of truncated biphalin analogs with a shortened second arm or with its replacement with another pharmacophore [ 25 , 26 , 27 , 28 ]. It was shown that even the hydrazide of tetrapeptide (H-Tyr-D-Ala-Gly-Phe-NH-NH 2 ) exhibited a good affinity for MOR, similar to the affinity of biphalin, but this compound had a 100 times lower affinity for DOR.…”
Section: Chemistry and Pharmacology Of Biphalinmentioning
confidence: 99%